Impact of allergic diseases on fertility - Wasilewska, Eliza; Małgorzewicz, Sylwia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2019)
The incidence of allergic diseases has been increasing in recent decades, and currently, nearly 30% of the European population suffer from some type of allergy. Also, an increasing number of people are suffering from infertility. Both diseases are related to the hormonal and immune systems, which prompts the question as to whether there is a causal relationship between allergic disorders and the reproductive system. The purpose of this review is to evaluate whether there is a link between allergic diseases and infertility, using the available literature.